Enhanced Endodontic Retreatment of A Maxillary Central Incisor Using Eucalyptol and The ProTaper Universal System: A Case Report - Oktayani, Runi; Hatta, Ridhayani; Muslim, Ichwanul; Djauharie, Nilakesuma (FKG Universitas Syiah Kuala, 2025)
Root canal treatment aims to eliminate infected pulp tissue and prevent further spread of infection. Howeever, initial root canal treatments does not always result in successful healing, potentially leading to post-treatment endodontic disease (PTED). This case report describes the non-surgical retreatment of a maxillary central incisor diagnosed with chronic apical periodontitis due to inadequate previous root canal treatment. A combination of eucalyptol solvent and the ProTaper Universal Retreatment System was used to enhance the removal of gutta-percha from the root canal. The retreatment approach improved clinical outcomes, with successful canal cleaning and disinfection. The use of eucalyptol can accelerate the dissolution process of gutta-percha compared to other solvents. Meanwhile, the use of the ProTaper Universal Retreatment system optimizes working time, making it faster than manual technique. Follow-up evaluations revealed favorable results, with the patient being scheduled for prosthetic restoration.